Data on erosion and hydrogen fuel retention in Beryllium plasma-facing materials. (June 2021) - De Temmerman, Gregory; Heinola, Kalle; Borodin, Dmitriy; Brezinsek, Sebastijan; Doerner, Russell P.; Rubel, Marek; Fortuna-Zaleśna, Elżbieta; Linsmeier, Christian; Nishijima, Daisuke; Nordlund, Kai; Probst, Michael; Romazanov, Juri; et al.
Abstract: ITER will use beryllium as a plasma-facing material in the main chamber, covering a total surface area of about 620 m 2 . Given the importance of beryllium erosion and co-deposition for tritium retention in ITER, significant efforts have been made to understand the behaviour of beryllium under fusion-relevant conditions with high particle and heat loads. This paper provides a comprehensive report on the state of knowledge of beryllium behaviour under fusion-relevant conditions: the erosion mechanisms and their consequences, beryllium migration in JET, fuel retention and dust generation. The paper reviews basic laboratory studies, advanced computer simulations and experience from laboratory plasma experiments in linear simulators of plasma–wall interactions and in controlled fusion devices using beryllium plasma-facing components. A critical assessment of analytical methods and simulation codes used in beryllium studies is given. The overall objective is to review the existing set of data with a broad literature survey and to identify gaps and research needs to broaden the database for ITER.